2007
DOI: 10.1523/jneurosci.1321-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Movement from Multiunit Activity

Abstract: Previous studies have shown that intracortical activity can be used to operate prosthetic devices such as an artificial limb. Previously used neuronal signals were either the activity of tens to hundreds of spiking neurons, which are difficult to record for long periods of time, or local field potentials, which are highly correlated with each other. Here, we show that by estimating multiunit activity (MUA), the superimposed activity of many neurons around a microelectrode, and using a small number of electrode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
266
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 285 publications
(282 citation statements)
references
References 42 publications
15
266
1
Order By: Relevance
“…Several studies have shown that the tuning properties of multiunits are similar to single units (Desimone and Gross, 1979;Super and Roelfsema, 2005;Zeitler et al, 2006;Stark and Abeles, 2007). Our data confirm this view for grasping in AIP and F5.…”
Section: Multiunit Signalssupporting
confidence: 90%
See 3 more Smart Citations
“…Several studies have shown that the tuning properties of multiunits are similar to single units (Desimone and Gross, 1979;Super and Roelfsema, 2005;Zeitler et al, 2006;Stark and Abeles, 2007). Our data confirm this view for grasping in AIP and F5.…”
Section: Multiunit Signalssupporting
confidence: 90%
“…Waveforms were thus pooled into a larger "multiunit" that comprised recordings from several individual neurons simultaneously. However, care should be taken to distinguish this point-process signal from continuous "multiunit activity" data generated from envelope functions applied to the low-pass-filtered voltage trace (Super and Roelfsema, 2005;Stark and Abeles, 2007;Choi et al, 2010). Finally, the predominance of multiunit recordings in our data set was in part due to the fixed (nonmovable) nature of the electrodes, which did not allow optimization of unit isolation during recordings.…”
Section: Off-line Data Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…It can be generated simply by thresholding extracellular voltage signals, and thus avoids computationally costly spike sorting algorithms [40]. It has been shown that in the motor cortex multi-unit activity of a single channel may carry a similar amount of information about a movement as the single units extracted from the same recording channel [3], [41].…”
Section: Discussionmentioning
confidence: 99%